2013
DOI: 10.1002/jmv.23551
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphism in MicroRNA 219‐1 with clearance of hepatitis B virus infection

Abstract: Polymorphisms in the primary microRNA region may be associated with natural course of hepatitis B virus (HBV) infection. This study evaluated if the mircoRNA 219-1 (miR-219-1) polymorphism can influence the susceptibility towards persistence of HBV infection and the progression to hepatocellular carcinoma (HCC) in patients with chronic HBV infection. A total of 1,439 individuals having either past or present evidence of HBV infection were enrolled for the study. The subjects were divided into four groups; (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…After initial denaturation at 95 °C for 10 min, samples were amplified through 40 cycles (92 °C for 15 s, 60 °C for 1 min). Primer and probe sequences of the two lociwere used according to the description by Guella et al [32] and Cheong et al [33] , respectively. In order to validate the result, 5% PCR products were randomly selected to DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…After initial denaturation at 95 °C for 10 min, samples were amplified through 40 cycles (92 °C for 15 s, 60 °C for 1 min). Primer and probe sequences of the two lociwere used according to the description by Guella et al [32] and Cheong et al [33] , respectively. In order to validate the result, 5% PCR products were randomly selected to DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…To serve as primary patients for the case-control study, a total of 1,439 individuals, having either past or present evidence of HBV infection, were recruited from the outpatient clinic of the liver unit and the Center for Health Promotion Center at Seoul National University Hospital, as well as Ajou University Hospital. Spontaneously recovered subjects were defined by a repeated seropositivity for both anti-HBs (antibody to hepatitis B surface antigen) and anti-HBc (antibody to hepatitis B core antigen) of the IgG type without HBsAg ( 10 ). The chronic carrier group was evaluated further for disease progression to cirrhosis or occurrence of HCC.…”
Section: Methodsmentioning
confidence: 99%
“…Using the Wizard genomic DNA purification kit (Promega, Madison, WI, USA), genomic DNA was extracted from patients' peripheral blood samples. SNP genotyping was performed using the TaqMan® ( 12 ) assay in the ABI prism 7900HT sequence detection system (Applied Biosystems, Foster City, CA, USA), as previously described ( 10 ). Genotyping quality control was performed in 10% of the samples, by duplicate checking (rate of concordance in duplicates=100%).…”
Section: Methodsmentioning
confidence: 99%
“…In a case-control study from Korea, Cheong et al [ 69 ] found that the T allele on the miR-604 gene served as a protective factor for the occurrence of HCC in patients with HBV-related chronic liver disease. In another independent study they found the T allele in the miR-219-1 promoter to be strongly associated with HBV clearance [ 70 ]. On the other hand, Kou et al [ 71 ] found that the miR-196a2C>T polymorphism imparts protection in HBV-related HCC.…”
Section: Mirna Polymorphism and Hbv Infectionmentioning
confidence: 99%